The ultrasound assisted hydration as an opportunity to incorporate nutrients into grains - Miano A.C. (2018)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding project n° 2016/18052-5; the National Council for Scientific and Technological Development (CNPq, Brazil) for funding project n° 401004/2014-7; and Cienciactiva for the A.C. Miano Ph.D. scholarship, from the “Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica” (CONCYTEC, Peru; Contract 272-2015-FONDECYT).